Effects of Myofascial Release and Neuromuscular Taping (NMT) on Decreasing Pain in The Condition Myofascial Pain Syndrome Upper Trapezius Muscle - Yose Rizal; Sari Triyulianti; Ruswaldi Munir (UNIVERSITAS NEGERI MAKASSAR, 2024)
Myofascial pain syndrome (MPS) refers to soft tissue pain resulting from irritation of local points within the skeletal muscle and myotendinous junctions. MTP produces pain with any activating stimulus (direct or indirect trauma), causing local and referred pain, tenderness, motor dysfunction, autonomic phenomena, and hyperexcitability of the central nervous system. This study aimed to determine the effectiveness of Neuromuscular Taping (NMT) and Myofascial Release (MR) intervention in reducing pain in patients with Myofascial Pain Syndrome of the Upper Trapezius Muscle. Methods: Case study with pre and post-test research design that compares the pain values before and after being measured with a measuring instrument Visual Analog Scale (VAS) to determine the effect of Myofascial Release (MR) and Neuromuscular Taping (NMT) on the condition of Myofascial Pain Syndrome in the Upper Trapezius Muscle for 4 weeks Result: the results of the Wilcoxon test analysis indicated that P<0.05, with a P value of 0.000. Therefore, it was determined that in patients with Upper Trapezius Muscle Myofascial Pain Syndrome, there was a difference in pain levels before and after receiving physiotherapy techniques such as Neuromuscular Taping (NMT) and Myofascial Release (MR).